Evaluasi Maturitas Sumber Daya Teknologi Informasi Bidang Aplikasi dan Infrastruktur Informatika Dinas Komunikasi dan Informatika Kota Mojokerto menggunakan Cobit 5 dengan Domain EDM04, APO07 dan BAI09 - Ainur Rosyid; Buce Trias Hanggara; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mojokerto City Communication and Informatics Office is an implementer under the elements of the Mojokerto city government that has the task to help the mayor carry out the duties of decentralization authority, deconcentration, and auxiliary duties in the field of communication and informatics. There is a problem in the management of IT resources there are no planning documents and control documents related to the problem that occurred, so the follow-up is done based on experience and has not been well documented. Other obstacles are the management of human resources (HR) that has not been optimal. Still Lack knowledge and understandi ng of information technology so it can affect the performance of each indi vidual that can impact the organization. Evaluation of information technology governance in its resource management section needs to be done to overcome problems or obstacles that occur at this time at the Office of Communication and Informatics MojokertoCity. The evaluation was conducted using COBIT 5 subdomains EDM04 (Ensure Resource Optimisation), APO07 (Manage Human Resource), and BAI09 (Manage Assets). The result of the evaluation on the management of IT resources in the Department of Communication and Informatics in Mojokerto city is the value of capability level EDM04 is at level 1, APO07 is at level 1, and BAI09 is at level 1. Gap level capability is 1 level each, namely at level 1 in domain EDM04, APO07, and BAI09. Recommendations given are Making documentation in the form of reports and Standard Operating Procedure (SOP) IT resources, Making human resource evaluation documents that can be a checklist sheet of work and targets for the week, and recordi ng in the study of IT assets in meeting business needs.